Penanggulangan Malaria Oleh Tim Jumantik Di SDN INPRES Arso 8 Kabupaten Keerom - Assa, Inriyanti; Asmuruf, Frans Augusthinus; Bouway, Dolfinus Yufu; Pangayow, Bill J.C; Kawulur, Hanna S; Bowaire, Anike N; Yufuai, Agustina; Tuturop, Katarina L; Pariaribo, Konstantina M; Rumbiak, Helmin; Ratnasariani, Widyawati; Mamoribo, Sherly N; Ramandey, Sherly; Simanjuntak, Lamria (The Community Engagement Journal, 2024)
Dengue hemorrhagic fever, malaria, filariasis are several diseases that are mediated by mosquitoes and are endemic diseases in several regions of Indonesia including Papua. Data in 2016 stated that Keerom Regency ranked first in the district with the highest API in Indonesia, which was 431 per 1000 population and 13% of malaria cases in Indonesia and 20% of malaria cases in Papua. Jumantik training activities are coaching activities for children with the aim of introducing and explaining to children about dengue fever and its prevention, as well as increasing children's awareness and participation to carry out PSN in their neighborhoods. So it is hoped that there will be a decrease in the number of malaria cases in Papua. Keywords: Malaria, Jumantik, Papua